Rate of speech in different Indian languages - N, Rathna (Journal of All India Institute of Speech and Hearing)
Rate of speaking is traditionally described as the number of words spoken per minute during a complete speech performance (Kelly and Steev, 1949). This would include all pauses intentional and unintentional and the meaningful words spoken in unit elapsed time. Recent investigation has indicated a relationship between syllable duration and speaker intelligibility. Even laymen seem to link up unintelligibility with rate of speech though it is often mentioned in the converse relationship. They seem to infer a faster rate of speech is unintelligible. Any tourist in foreign countries must have had the complaint that the tourist speaks very fast while he himself felt that the natives were very fast. Actually they were both saying that they do not understand each other. It has often been claimed that Indian languages, the South Indian language in particular are very fast